Perancangan sistem Perawatan Aquaponik Tanaman Cabe Rawit Dan Ikan Lele Menggunakan Arduino Berbasis Internet Of things - Setiawan, Nuris Dwi (LPPM UNIKA Santo Thomas, 2020)
require a large area, but there are still problems, namely in terms of watering, but there are still problems with the aquaponic plant care system, the manual system used has not been able to detect turbidity in the water in the pond catfish, detecting water pH in fish ponds, temperature detecting water in catfish ponds automatically and in real time, this requires cultivators to check water conditions continuously, this is quite troublesome. From the existing problems, it is necessary to have an intelligent system that can monitor the aquaponics system in real time and with precision. One of them is to use a smart system using an Arduino based on the Internet of Things. The tool used is Arduino. Arduino functions to process signals from the ds18b20 temperature sensor, turbidity sensor, and water pH as components and to display a 16x2 LCD. Arduino is implemented with a program that functions as an initializer and hardware configuration as well as reading signals and input from the temperature sensor and cloudy, pH water which then processes it given several conditions to produce information and display the LCD. The results of the study can control the temperature sensor, cloudiness, pH of the water, automatically in the aquaponic system maintenance, the measurements obtained from the sensors installed in the Cayenne Pepper and Catfish Treatment System Using the Arduino-Based Aquaponic Method. The light will be active when the temperature is not normal, and if the water is cloudy, the pH is not normal, the red light will be on.